The National and University Library in Ljubljana - the intersection of Time and Cultures - Mušič, Marko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
As any important architectural work, the libraries from the distant past are vivid organisms that bear in themselves the biological, historical and humanistic experience. Those who live with, and use, such architecture feel its spiritual energy and its vital palpitation. The space accepts them and through symbols and rituals it passes on their idea; it passes on the situation today, however, this is performed from its yesterday’s and tomorrow’s position. Therefore, good library architecture does not follow changes in trends and fashion, but lives its own time in the continuum of historical consciousness, revealing the spirit and importance of its existence. In the architectural Renaissance taking place during the last years libraries became exactly the same as the important buildings throughout history used to be. They are prestigious architectural achievements that became the visual and symbolic signs of national pride, the cathedrals of our days.